Các hợp chất pterocarpan phân lập từ gỗ cây cẩm lai (Dalbergia oliveri Gamble ex Prain) - Loan, Phạm Thanh; Thái, Trần Huy; Kiệm, Phan Văn; Anh Tuấn, Hoàng Lê; Minh, Châu Văn; Nhiệm, Nguyễn Xuân; Thúy Hằng, Đan Thị; Hải Yến, Dương Thị; Cúc, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Three pterocarpan-type flavonoids: 3-hydroxy-8,9-methylenedioxypterocarpan (1), 3,8-dihydroxy-9-methoxypterocarpan (2), and 3-hydroxy-9-methoxypterocarpan (3) were isolated from the ethyl acetate extract of heartwood of the Dalbergia oliveri by various chromatographic experiments. Their structures were elucidated using 1D, 2D NMR spectroscopic methods and in comparison with the literature values. This is the first report of compounds 2 and 3 from D. oliveri. Keywords: Dalbergia oliveri, pterocarpan.